2022
DOI: 10.21037/tau-21-814
|View full text |Cite
|
Sign up to set email alerts
|

Educational value assessment of YouTube surgical videos of tension-free vaginal tape obturator (TVT-O) and trans-obturator vaginal tape (TOT)

Abstract: Background: YouTube, as a widely used video website around the world, contains a large number of surgical teaching videos, providing a good platform for doctors to learn surgery, but its content and quality are uneven. Tension-free vaginal tape obturator (TVT-O) and trans-obturator vaginal tape (TOT) are common surgical methods for the treatment of stress urinary incontinence (SUI), and there are many videos on YouTube teaching these procedures. We aimed to assess the educational value of surgical videos of TV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, there was no comparison between the videos according to the sources. Chen et al 20 investigated the value of surgical videos of tension‐free vaginal tape obturator (TVT‐O) and trans‐obturator vaginal tape (TOT) using a checklist. They concluded that educational videos about TVT‐O and TOT were still lacking, and available videos were insufficient to explain critical steps of surgery, perioperative complications and management, and application of procedural tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there was no comparison between the videos according to the sources. Chen et al 20 investigated the value of surgical videos of tension‐free vaginal tape obturator (TVT‐O) and trans‐obturator vaginal tape (TOT) using a checklist. They concluded that educational videos about TVT‐O and TOT were still lacking, and available videos were insufficient to explain critical steps of surgery, perioperative complications and management, and application of procedural tools.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was no comparison between the videos according to the sources. Chen et al 20 of procedural tools. In a recent study, the comprehensibility and quality of contents on pelvic organ prolapse for patients on Pinterest, Instagram, and YouTube were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a challenge for ensuring educational quality because YouTube video upload has low entry barriers and lacks a comprehensive supervision and evaluation system compared with the official surgical videos with strict access permission provided by some medical schools, resulting in varying quality of existing teaching videos on TURP surgery, and the overall quality level is yet to be determined. As a result, young surgeons may learn techniques and concepts incorrectly, which can have disastrous consequences for patients ( 10 ).…”
Section: Introductionmentioning
confidence: 99%